Experimental study of an innovative elastomer-based heat exchanger - Souza, R. R.; Sá Barbosa, F. M.; Nobrega, G.; Cardoso, E. M. [UNESP]; Teixeira, J. C.F.; Moita, A. S.; Lima, R. (Elsevier, 2023)
This work aims to present the development stages of a serpentine heat exchanger, composed uniquely of a thin layer of a silicon-based organic elastomeric polymer, polydimethylsiloxane (PDMS). The novelty of this heat exchanger is that it allows the flowing liquid to wet the surface to be cooled directly, an innovation in relation to traditional exchangers, generally made up of tubes coupled to the heating surfaces. In order to evaluate its thermal performance, experimental flow tests compared two PDMS serpentines with a hydraulic diameter of around 5.0 mm with a traditional tubular copper serpentine. The heat exchanger made of PDMS was coupled to a steel plate that simulated the rear side of a photovoltaic thermal solar panel (PVT). In addition, different geometries were tested. Although PDMS is considered a material of low thermal conductivity, the experimental results showed a greater cooling capacity when compared to the traditional heat exchanger reducing the surface's temperature by an average of 17%. Though the experimental results presented here were obtained for a specific case, the innovation can be used for thermal control of central process units (CPUs), smartphones, tablets, video games, and other mechanical and electronic devices with high cooling requirements.
Keywords: Heat exchanger; Heat transfer; PDMS serpentine; Polydimethylsiloxane; Thermal conductivity